Formulation of Joint Property Agreement: Civil Code, Balinese Customary Law, and Transcendental Justice - Gunanta, I Gede; Erwin, Yulias; Septyanun, Nurjannah (Journal of Transcendental Law, 2025)
The issue of joint property agreements in marriage is an important issue in family law, especially when divorce occurs. In the context of Indonesia's positive law, the regulation of common property normatively refers to the Civil Code (KUHPercivil), especially Articles 119 to 128. However, in practice in indigenous peoples, especially Balinese people who adhere to Balinese Hindu Customary Law, the arrangement and understanding of common property has different values, norms, and structures, which are often not fully recognized in the national legal system. This normative gap raises conceptual issues regarding the recognition and legal protection of joint property agreements in two different legal systems. This research uses a normative legal approach, with legal sources coming from legislation, judges' decisions. Furthermore, legal materials are analyzed using interpretive descriptive and analytical descriptive. The results of the study show that the common property agreement must not only fulfill the elements of the validity of the agreement in a positive legal manner, but must also reflect the values of justice that live in society, especially transcendental justice, which is justice that comes from religious and spiritual values that are upheld in Balinese Hindu customs. So that the ideal formulation of the concept of a common property agreement is to integrate the normative elements of the Civil Code with Balinese Hindu customary law practices. The binding power of mutual price agreements in the context of juridical and transcendental justice, becomes a form of reconstruction of family law that recognizes the plurality of laws and places substantive and spiritual values of justice as the basis for binding agreements, without ignoring the principles of legality and formal legal validity